Willingness to Pay For Water at Household Level in Ilorin, Kwara State, Nigeria. (Global Journal of Human-Social Science, 2011)
The paper examines willingness to pay WTP at the level of household in Ilorin Nigeria Ilorin was divided into four residential zones namely Government Reservation Area GRA Modern Area Housing Estates and Traditional Area 50 questionnaires were administered in each of these zones making a total of 200 questionnaires administered in the whole of the study area Also 37 socio-economic variables were generated from the questionnaire Due to multicolinearity problem factor analysis method was used to reduce the 37 variables to orthogonal factor defining variables Multiple regression analysis was used to associate willingness to pay WTP and the social economic variables The result of factor analysis showed that 3 factor defining variables fdvs income demography and educational level are the most dominant factors having 98 explanation Further analysis through stepwise multiple regression suggests that household income is the best predictor of WTP in Ilorin with 83 explanation The paper posits that any policy towards pricing water in Ilorin should consider household income as an important variant
Keywords: household in Ilorin; socio-economic